Drug Resistance-Related Competing Interactions of lncRNA and mRNA across 19 Cancer Types - Haizhou Liu; Shuyuan Wang; Shunheng Zhou; Qianqian Meng; Xueyan Ma; Xiaofeng Song; Lihong Wang; Wei Jiang (Elsevier, 2019)
Drug resistance is a common cause of treatment failure in cancer therapy, and molecular mechanisms need further exploration. Competing endogenous RNAs (ceRNAs) can influence drug response by participating in various biological processes, including regulation of cell cycle, signal transduction, and so on. In this study, we systematically explored resistance from the perspective of ceRNA modules. First, we constructed a general ceRNA network, involving 83 long non-coding RNAs (lncRNAs) and 379 mRNAs. Next, we identified the drug resistance-related modules for 138 drugs and 19 cancer types, totaling 758 drug-cancer conditions. Function analysis showed that resistance-related biological processes were enriched in these modules, such as regulation of cell proliferation, DNA damage repair, and so on. Pan-drug and pan-cancer analyses revealed some common and specific modules across multiple drugs or cancers. In addition, we also found that drug pairs with common modules have similar structure, indicating high risk for multidrug resistance (MDR). Finally, we speculated that ceRNA pair GAS5-RPL8 could regulate drug resistance because low expression of GAS5 would enhance microRNA (miRNA)-mediated inhibition of RPL8. In total, we investigated the drug resistance by using ceRNA modules and proposed that ceRNA modules may be new markers for drug resistance that indicated a possible novel mechanism. Keywords: drug resistance, pan-cancer, pan-drug, ceRNA, network module, lncRNA